Exogenous Nicotinamide Adenine Dinucleotide Induces Resistance to Citrus Canker in Citrus - Alferez, Fernando M.; Gerberich, Kayla M.; Li, Jian-Liang; Zhang, Yanping; Graham, James H.; Mou, Zhonglin (Frontiers in Plant Science, 2018)
Nicotinamide adenine dinucleotide (NAD) is a universal electron carrier that participates in important intracellular metabolic reactions and signaling events. Interestingly, emerging evidence in animals indicates that cellular NAD can be actively or passively released into the extracellular space, where it is processed or perceived by ectoenzymes or cell-surface receptors. We have recently shown in Arabidopsis thaliana that exogenous NAD induces defense responses, that pathogen infection leads to release of NAD into the extracellular space at concentrations sufficient for defense activation, and that depletion of extracellular NAD (eNAD) by transgenic expression of the human NAD-hydrolyzing ectoenzyme CD38 inhibits plant immunity. We therefore hypothesize that, during plant–microbe interactions, NAD is released from dead or dying cells into the extracellular space where it interacts with adjacent naïve cells’ surface receptors, which in turn activate downstream immune signaling. However, it is currently unknown whether eNAD signaling is unique to Arabidopsis or the Brassicaceae family. In this study, we treated citrus plants with exogenous NAD+ and tested NAD+-induced transcriptional changes and disease resistance. Our results show that NAD+ induces profound transcriptome changes and strong resistance to citrus canker, a serious citrus disease caused by the bacterial pathogen Xanthomonas citri subsp. citri (Xcc). Furthermore, NAD+-induced resistance persists in new flushes emerging after removal of the tissues previously treated with NAD+. Finally, NAD+ treatment primes citrus tissues, resulting in a faster and stronger induction of multiple salicylic acid pathway genes upon subsequent Xcc infection. Taken together, these results indicate that exogenous NAD+ is able to induce immune responses in citrus and suggest that eNAD may also be an elicitor in this woody plant species.